2016
DOI: 10.1155/2016/3284087
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Home-Based Early Intervention for Autism in Sri Lanka: Follow-Up of a Cohort and Comparison with a Nonintervention Group

Abstract: This paper presents the outcome of a home-based autism intervention program (HBAIP) in 18- to 40-month-old children newly diagnosed and treatment naïve. Intervention was exclusively implemented at home. Outcome was measured at 3 months and 6 months after intervention and compared with a group of newly diagnosed children with autism who were >40 months at intake but had not received any autism specific clinical management. Aim was also to estimate whether natural development would contribute to gain in skills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
0
22
0
13
Order By: Relevance
“…Parent based education program helps caregivers to interact and communicate with their children with ASD and promote the development of their children's communication and behavioral skills, parent-child interaction, as well as parent well-being [Beaudoin, Sébire, & Couture, 2014]. Recent studies in China and Sri Lanka suggest that home-based parental training programs through play activity, as well as music therapy, can improve child-related outcomes such as communication, daily living skills, eye contact, and social reciprocity [Liao et al, 2014;Perera, Jeewandara, Seneviratne, & Guruge, 2016;Yang, 2016].…”
Section: New Evidence Of Asd In Relevance To Lmic and Contextualizatimentioning
confidence: 99%
See 1 more Smart Citation
“…Parent based education program helps caregivers to interact and communicate with their children with ASD and promote the development of their children's communication and behavioral skills, parent-child interaction, as well as parent well-being [Beaudoin, Sébire, & Couture, 2014]. Recent studies in China and Sri Lanka suggest that home-based parental training programs through play activity, as well as music therapy, can improve child-related outcomes such as communication, daily living skills, eye contact, and social reciprocity [Liao et al, 2014;Perera, Jeewandara, Seneviratne, & Guruge, 2016;Yang, 2016].…”
Section: New Evidence Of Asd In Relevance To Lmic and Contextualizatimentioning
confidence: 99%
“…Maternal mental health supports in ASD care and QoL. Studies conducted in both the high resource and LMIC settings have reported that parents who participated in any training interventions for their children with ASD consistently report a high degree of satisfaction and improvement in their children [Patterson & Smith, 2011;Perera et al, 2016;Rahman et al, 2016]. However, higher socioeconomic status of mothers and improvement in children after schooling were important contributory factors for the improvement of the QoL of mothers in our study, suggesting affordability of the families to offer ASD care through school services may influence QoL of mothers of children with ASD, and more representative studies will be needed to further parse such a relationship.…”
Section: New Evidence Of Asd In Relevance To Lmic and Contextualizatimentioning
confidence: 99%
“…Perera, Jeewandara, Seneviratne, and Guruge [28] investigated an early-intervention program for children aged 18 to 40 mon in Sri Lanka. Study participants were children who had just received an initial diagnosis of Autism, were 18 to 40 mon in age, and had never received behavioral or developmental intervention previously.…”
Section: Restrictive Exclusion Criteriamentioning
confidence: 99%
“…Destacou-se sobre a eficácia e viabilidade das intervenções precoce em crianças com TEA, e a importância do uso de intervenção desde o início dos sinais de alerta (D'Elia et al 2014;Howard et al 2014;Kasari et al 2015;Kitzerow, et al 2019;Perera et al 2016;Rogers et al 2014;Yatawara et al 2016). O uso de tecnologia combinada a intervenções precoce, que representa uma ferramenta de grande utilidade no tratamento de crianças com TEA, sendo utilizadas tanto pelos pais como pelos profissionais (Moore et al 2015;Whitehouse et al 2017).…”
Section: Pubmed A13unclassified
“…O transtorno do espectro autista provoca grandes déficits comunicativos e afetivos, em decorrência de tais problemas a maioria das intervenções precoces são voltadas para o desenvolvimento e melhoria de tais habilidades (Mottron, 2017;Perera et al, 2016). Dentre as intervenções precoces mais utilizadas atualmente destaca-se as intervenções comportamentais e naturalista que tem como foco a intensidade e a precocidade da intervenção (Kasari et al, 2015;Kitzerow et al, 2019;Howard et al, 2014;Mottron, 2017).…”
Section: O Uso De Intervenção Precoce Em Crianças Com Teaunclassified